Evolution of Divergent Life History Strategies in Marine Alphaproteobacteria - Luo, Haiwei (American Society of Microbiology, 2013)
Marine bacteria in the Roseobacter and SAR11 lineages successfully exploit the ocean habitat, together accounting for ~40% of bacteria in surface waters, yet have divergent life histories that exemplify patch-adapted versus free-living ecological roles. Here, we use a phylogenetic birth-and-death model to understand how genome content supporting different life history strategies evolved in these related alphaproteobacterial taxa, showing that the streamlined genomes of free-living SAR11 were gradually downsized from a common ancestral genome only slightly larger than the extant members (~2,000 genes), while the larger and variably sized genomes of roseobacters evolved along dynamic pathways from a sizeable common ancestor (~8,000 genes). Genome changes in the SAR11 lineage occurred gradually over ~800 million years, whereas Roseobacter genomes underwent more substantial modifications, including major periods of expansion, over ~260 million years. The timing of the first Roseobacter genome expansion was coincident with the predicted radiation of modern marine eukaryotic phytoplankton of sufficient size to create nutrient-enriched microzones and is consistent with present-day ecological associations between these microbial groups. We suggest that diversification of red-lineage phytoplankton is an important driver of divergent life history strategies among the heterotrophic bacterioplankton taxa that dominate the present-day ocean.